2013
DOI: 10.1186/1756-6606-6-48
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological enhancement of mGlu1 metabotropic glutamate receptors causes a prolonged symptomatic benefit in a mouse model of spinocerebellar ataxia type 1

Abstract: BackgroundSpinocerebellar ataxia type 1 (SCA1) is a genetic disorder characterized by severe ataxia associated with progressive loss of cerebellar Purkinje cells. The mGlu1 metabotropic glutamate receptor plays a key role in mechanisms of activity-dependent synaptic plasticity in the cerebellum, and its dysfunction is linked to the pathophysiology of motor symptoms associated with SCA1. We used SCA1 heterozygous transgenic mice (Q154/Q2) as a model for testing the hypothesis that drugs that enhance mGlu1 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 63 publications
3
81
0
Order By: Relevance
“…185188 However, as the only available mGlu 1 PAM in vivo tool, it has been employed to preclinically validate mGlu 1 in multiple CNS disorders. 189192 With the new emphasis on genetic basis of disease, two recent, independent studies identified 12 rare, deleterious nonsynonymous single-nucleotide polymorphisms (nsSNPs) in the GRM1 gene, which encodes mGlu 1 , in schizophrenic patients; this has renewed interest in mGlu 1 PAMs, as these mutations were shown to be loss of function. 193,194 Work from the Vanderbilt group has characterized the mutant mGlu 1 receptors and demonstrated that 38 could indeed potentiate their response to glutamate and, in some instances, restore signaling.…”
Section: 1 Allosteric Modulators Of the Mglu1 Receptormentioning
confidence: 99%
“…185188 However, as the only available mGlu 1 PAM in vivo tool, it has been employed to preclinically validate mGlu 1 in multiple CNS disorders. 189192 With the new emphasis on genetic basis of disease, two recent, independent studies identified 12 rare, deleterious nonsynonymous single-nucleotide polymorphisms (nsSNPs) in the GRM1 gene, which encodes mGlu 1 , in schizophrenic patients; this has renewed interest in mGlu 1 PAMs, as these mutations were shown to be loss of function. 193,194 Work from the Vanderbilt group has characterized the mutant mGlu 1 receptors and demonstrated that 38 could indeed potentiate their response to glutamate and, in some instances, restore signaling.…”
Section: 1 Allosteric Modulators Of the Mglu1 Receptormentioning
confidence: 99%
“…However, as the only mGu 1 PAM tool compound with CNS exposure, the field had no other option than to employ the lone existing tool to validate and understand the receptor’s role in numerous CNS disorders. 1720 Thus, to provide an mGlu 1 PAM in vivo tool compound with a more desired profile ( F u > 3%, K p > 0.8, clean CYP profiles) to ensure robust target engagement and validation, as well as a distinct chemotype to avoid chemo-type-related pharmacology, our lab has recently focused on the development of next generation mGlu 1 PAMs and ago-PAMs.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, silencing the SCA1 transgene restored both mGlu 1 receptor expression and motor function, suggesting a causative role of this signaling pathway in ataxic symptoms (Zu et al, 2004). The reduction in the expression of mGlu 1 receptor mRNA and protein levels in a SCA1-model mouse with severe ataxia was confirmed by Notartomaso et al (2013). Treatment of these mice with a positive allosteric modulator of the mGlu 1 receptor caused a long-lasting improvement of motor performance (Notartomaso et al, 2013).…”
Section: Alterations Of the Parallel Fiber-purkinje Cell Synapse In Nmentioning
confidence: 59%
“…The reduction in the expression of mGlu 1 receptor mRNA and protein levels in a SCA1-model mouse with severe ataxia was confirmed by Notartomaso et al (2013). Treatment of these mice with a positive allosteric modulator of the mGlu 1 receptor caused a long-lasting improvement of motor performance (Notartomaso et al, 2013). However, in these studies, the mGlu 1 -EPSC was not assessed, so that the role of mGlu 1 -mediated synaptic signaling at the PF-PC synapse remains uncertain.…”
Section: Alterations Of the Parallel Fiber-purkinje Cell Synapse In Nmentioning
confidence: 59%